Kaji Sistem pengering Kakao dengan Menggunakan Energi Hybrid (Energi Matahari dan Bahan Bakar Gas) - Ahmad Syuhada; Ratna Sary; Farid Isnan (Jurnal Teknik Mesin Unsyiah, 2018)
Cocoa one of the agricultural commodity which grow well that in Aceh and could producing the fruit for the rest of the year. In 2017, the wide of productive area reached 98,233 hectares (HA). The result of the crop was capable attained 32,403 tons/year. However, due to Aceh has climate tropical, when the dry season came, the drying process was still could on processing but when rainy season came, the drying process will be hampered and if the weather was still not sunny probaly it could make the fungus appeared. The aim of the research was to get the more optimal drying system so that it could be used when it was dry or rainy. The research described about drying system with 3 drying methods that is solar collector dryer, combustion dryer and hybrid dryer. From the result which conducted on 16 kg using a solar collector, the drying time was 25 hours with total energy used was 23.491,01 Kj. On the trial used hybrid energy, the drying time was 19 hours which total energy used was 160.636,19 Kj. On the trial used combustion energy, the drying time reached 14 hour with total energy used was 184.546,58 kj. in concluions that hybrid energy could get the best result in colour, kakao aromatic that more scents, no fungus, and the the seed could not break so that it reach I SNI quality.